The Potential Perspective of Processing Rice Husk as SiO2 Source to Tetraalkoxysilane in Indonesia - Wahyudianto, Benny; Putro, Wahyu Saptrio; Nguyen, Thuy Thi Hong; Fukaya, Norihisa; Kataoka, Sho (Indonesian Journal of Chemistry, 2024)
Tetra-alkoxysilane (TROS) is one of the useful chemicals and it can be processed to produce semiconductor and photovoltaic devices. Now, the transformation of silica (SiO2) to TROS is garnering interest due to the potential of extracting it from biomass. As the 14th largest country, Indonesia possesses an abundant source of SiO2 from mining activities and agricultural waste, notably rice husk (RH). However, only a little concrete action is planned for leveraging RH into a more valuable industrial substance. This review will explain two routes for TROS—conventional and direct—comparing their respective benefits and drawbacks. Additionally, it presents a simulation of various scenarios for scaling TROS production to an industrial level, considering technoeconomic and environmental assessment aspects. The focus then shifts to Indonesia’s strategic trajectory for 2045, offering recommendations to enhance resource utilization for economic and national development.